2020
DOI: 10.3390/ma13153248
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Precipitate Microstructure Affecting Fatigue Behavior of 7020 Aluminum Alloy

Abstract: The effect of different precipitate microstructures obtained by different heat treatments on fatigue behavior of 7020 aluminum alloy was investigated. The fine Guinier Preston I (GPI) zones in the under-aged alloy can be repeatedly sheared by dislocations produced in cyclic loading, making the fatigue crack initiate difficultly and fatigue crack path propagate tortuously. Fatigue strength and fatigue crack propagation resistance of the alloy with shearable precipitates are much higher than those of the alloy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The fatigue properties of aluminum alloy joints play an important role in the safety and reliability of structural assemblies [ 6 ], with up to 90% of engineering constructions failing because of fatigue [ 7 ]. Researchers have found that excess solute Mg can improve the fatigue strength and fatigue life of 6xxx alloys [ 8 , 9 , 10 , 11 , 12 ]. Takahashi [ 9 ] reported that the fatigue strength and fatigue life of 6xxx alloys can be improved by adding excess Mg, so that Mg exists in solid solution in the matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue properties of aluminum alloy joints play an important role in the safety and reliability of structural assemblies [ 6 ], with up to 90% of engineering constructions failing because of fatigue [ 7 ]. Researchers have found that excess solute Mg can improve the fatigue strength and fatigue life of 6xxx alloys [ 8 , 9 , 10 , 11 , 12 ]. Takahashi [ 9 ] reported that the fatigue strength and fatigue life of 6xxx alloys can be improved by adding excess Mg, so that Mg exists in solid solution in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of β″ precipitates on the fatigue properties of Al-Mg-Si 6xxx alloys has been investigated [ 2 ], in which it was found that heat treatment significantly improves the fatigue strength of AA6061-T6 joints with ER4043 filler owing to the formation of β″ precipitates resulting from Mg via base metal dilution. Many studies have investigated the interactions between dislocations and precipitates [ 11 , 13 , 14 , 15 ]. Notably, because dislocations can shear coherent or semi-coherent precipitates, the number density of precipitates increases via shearing, leading to enhanced resistance against dislocation movement and hence increased fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…FCP curves of 7055 and 2219 Al alloys at different aging states, experimental results from refs., [26,27] respectively. a,c) 7055; b,d) 2219.…”
Section: Analyses and Discussionmentioning
confidence: 99%
“…Both 7075 and 2024 Al alloys should have the lowest FCP rate at the UA state if the effect of the aging state on FCP rate is explained in terms of dislocation slip reversibility as by previous studies. [25][26][27] However, this is not the case with the experimental results, which indicates that dislocation slip reversibility is not the main factor affecting the FCP rate. It is well known that the reversibility of dislocation slip at different aging states is dominated by microscopic deformation mechanisms.…”
Section: Fatigue Crack Propagation Behaviormentioning
confidence: 93%
See 1 more Smart Citation